2014
DOI: 10.1128/jvi.00265-14
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Increases Susceptibility to Heterologous but Not Homologous Secondary Influenza

Abstract: Asthma was the most common comorbidity observed among patients hospitalized with influenza A virus during the 2009 pandemic. However, little remains known about how the asthmatic phenotype influences protective immune responses against respiratory viral pathogens. Using the ovalbumin-induced allergic lung inflammation model, we found that asthmatic mice, unlike nonasthmatic mice, were highly susceptible to secondary heterologous virus challenge. While primary virus infection generated protective memory immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…We have recently reported that asthmatic mice are more susceptible to secondary heterologous challenge with CA04 virus [ 65 ]. In that study, we utilized a secondary influenza challenge model in which asthmatic mice were reinfected with influenza virus at week 6 post OVA challenge when TGF-β expression is at the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that asthmatic mice are more susceptible to secondary heterologous challenge with CA04 virus [ 65 ]. In that study, we utilized a secondary influenza challenge model in which asthmatic mice were reinfected with influenza virus at week 6 post OVA challenge when TGF-β expression is at the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…After the last exposure to the allergen or saline, in vivo airway muscle contractile response to the muscarinic agonist methacholine was assessed by measuring enhanced pause (Penh) using an unrestricted whole‐body plethysmography system (Buxco Research Systems, Wilmington, NC, USA) or newtonian resistance (Rn) using an FlexiVent (SCIREQ Scientific, Montreal, QC, Canada) system (5, 15).…”
Section: Methodsmentioning
confidence: 99%
“…The number of mouse models that use mice with established allergic inflammation for subsequent infection with IAV are limited ( 139 , 158 161 ), but have already provided important information regarding the pathogenesis of IAV in asthma relevant to the Swine Flu pandemic (Figure 5 ). Ishikawa et al found that ovalbumin-induced asthma protected mice from influenza, a phenomenon that they attributed to NK cells ( 161 ) (Figure 5 ).…”
Section: Proposed Mechanistic Insights On the Pathogenesis Of Asthma mentioning
confidence: 99%